Chemotherapy for dogs with lymph node metastasis from histiocytic sarcomas. Issue 1 (January 2017) - Moore, AS; Taylor, DP; Reppas, G; Frimberger, AE
Abstract : Background: Histiocytic sarcomas (HS) frequently metastasise, most commonly to visceral sites, but also to regional lymph nodes. Nodal metastases are associated with a poorer prognosis. This retrospective study aimed to evaluate prognostic factors, including the effect of adjuvant chemotherapy, on survival in dogs with nodal, but not systemic, metastases from HS. Methods: Retrospective case series of 12 dogs with histologically diagnosed HS metastatic to lymph nodes treated with surgery with and without adjuvant chemotherapy. Results: All dogs had histological evidence of metastasis to lymph nodes, with no clinical evidence for metastasis to viscera. Eight dogs that received chemotherapy had a median estimated survival of 219 days (range 77–1638 days); 1‐ and 2‐year estimated survival rates were 37.7%. Median survival time for 4 dogs with nodal metastases that did not receive chemotherapy was 57 days (range 39–136 days) with none alive 1 year after surgery Conclusion: Survival for dogs with only regional nodal metastases from HS appeared to be improved by adjuvant chemotherapy.